2007
DOI: 10.1002/prep.200700034
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Conventional Stabilizers and Phenol Compounds Used as Antioxidants on the Stabilization of Nitrocellulose

Abstract: The thermal behavior of nitrocellulose (NC) containing diphenylamine (DPA), 2-nitrodiphenylamine (2-NO 2 -DPA), N-nitrosodiphenylamine (N-NO-DPA), ethyl centralite (EC), akardite II (AKII), 1,1,3-tri-(2-methyl-4-hydroxy-5-tert-butyl-phenyl)-butane (BP less ), 3-(3,5-di-tert-butyl-4-hydroxy-phenyl)-propionic acid octadecyl ester (BP hin ), and 3-(3-tert-butyl-4-hydroxy-5-methylphenyl)-propionic acid 2-(9-{2-[3-(3-tert-butyl-4-hydroxy-5-methyl-phenyl)-propionyloxy]-1,1-dimethyl-ethyl}-2,4,8,10-tetraoxaspiro [5.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…Initial experiments on alkoxy-activated benzenes indicated that they work well as stabilizers, which confirmed published results [14][15][16][17][18].H owever, their relatively high vapor pressuresr ender them less suitable for commercial products. The use of av olatile stabilizer could lead to vaporization during the processing of the propellant and could either lead to al owers tabilizer content than desired in the final product or aw ork environment issue for the operators.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Initial experiments on alkoxy-activated benzenes indicated that they work well as stabilizers, which confirmed published results [14][15][16][17][18].H owever, their relatively high vapor pressuresr ender them less suitable for commercial products. The use of av olatile stabilizer could lead to vaporization during the processing of the propellant and could either lead to al owers tabilizer content than desired in the final product or aw ork environment issue for the operators.…”
Section: Introductionsupporting
confidence: 79%
“…Recently,v ariouss ubstitutedp henols were suggested as new stabilizers and exhibited promising but less stabilizing effect than the conventional stabilizers [14][15][16][17][18]. The investigated phenols werei nm ost cases sterically hindered with largea lkyl substituents present on the aromatic ring.…”
Section: Introductionmentioning
confidence: 99%
“…The latter two compounds are very similar in structure to 2,4‐ditertbutylphenol and butylated hydroxytoluene (BHT), which are commercially used as antiaging agents for natural and synthetic rubber, food preservatives, plastic antioxidants, fuel stabilizers, and ultraviolet absorbents 15, 16. The purpose of these phenolic antioxidants is to act as free radical scavengers to inhibit or slow the oxidative process through a recognized polymer autoxidation mechanism 17. These phenol antioxidant compounds have been shown to react with ROO .…”
Section: Resultsmentioning
confidence: 99%
“…Not only a reduction in the performances of the propellant will be observed, but self-ignition may ensue by accelerated decomposition caused by autocatalysis and/or by self-heating, posing important safety issues. This exothermic process has already caused numerous incidents in the propellant industry [3].…”
Section: Introductionmentioning
confidence: 99%
“…Many new stabilisers for propellant powders have been examined [6,7], such as hindered amines, e. g. triphenylamine (TPA) [8] and malonanilide derivatives [9], hindered phenols [3,[10][11][12], organic sulphur and phosphor organic compounds [13], and an activated aromatic ether (STAB-5) [14][15][16]. TPA is a tertiary amine and therefore does not have [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 any NÀH bonds, so that no carcinogenic N-nitrosamines can be formed [17].…”
Section: Introductionmentioning
confidence: 99%